2022
DOI: 10.3390/ijerph19106093
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokines and Insulin Resistance: Their Role as Benign Breast Disease and Breast Cancer Risk Factors in a High-Prevalence Overweight-Obesity Group of Women over 40 Years Old

Abstract: Insulin levels, adipocytokines, and inflammatory mediators trigger benign breast disease (BBD) and breast cancer (BC). The relationship between serum adipocytokines levels, overweight-obesity, metabolic disturbs, and BC is unclear. Methods: To analyze the serum levels of the adipocytokines, insulin, and the HOMA IR in women without breast disease, with BBD or BC, and the role of these as risk factors for benign breast disease or breast cancer. Results: Adipsin values > 0.91 and visfatin levels > 1.18 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…In other words, blocking the MAP kinase pathway could potentially stop cell growth while leaving the metabolic actions of the hormone unaffected, which would be particularly relevant in cases of breast cancer or colorectal cancer, where insulin promotes cell growth and proliferation in malignant clones. These conditions have been observed previously in our reports concerning insulin and adipocytokines in obese women with breast cancer [24].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In other words, blocking the MAP kinase pathway could potentially stop cell growth while leaving the metabolic actions of the hormone unaffected, which would be particularly relevant in cases of breast cancer or colorectal cancer, where insulin promotes cell growth and proliferation in malignant clones. These conditions have been observed previously in our reports concerning insulin and adipocytokines in obese women with breast cancer [24].…”
Section: Discussionsupporting
confidence: 87%
“…In our previously published article regarding normal adipocytokine values in healthy Mexican women over the age of 40 [24], we determined the results according to the following analytes and subrogated variables: leptin, adiponectin, resistin, visfatin, adipsin, and HOMA-IR (insulin = 2.6 mU/mL, leptin = 27.5 ng/mL, adiponectin = 17.68 mg/mL, resistin = 0.59 ng/mL, visfatin = 1.18 ng/mL, and adipsin = 0.91 mg/mL, HOMA-IR = 0.78) [21]. The current report determined the normal values based on the median and interquartile intervals for the key metabolic mediators and anthropometric characteristics (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms for the association of MAFLD with increased cancer risk have not been fully elucidated, but several hypotheses exist. First, insulin resistance, as the key determinant in the pathology of MAFLD, is involved in the dysregulation of insulin-like growth factors and might contribute to malignant transformation at various sites, including the liver, pancreas, colon and breast [40][41][42], by promoting cell proliferation and angiogenesis and inhibiting apoptosis [43,44]. Second, overweight/obesity, another main factor in MAFLD, may result in a state of chronic systemic low-grade inflammation attributed to a proinflammatory environment, which may affect cancer risk by increasing the formation of reactive oxygen species, increasing cell cycle rates, and decreasing tumor suppressor function [45].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have identi ed major risk factors for obesity, including demographic factors (race, sex, age), lifestyle factors (exercise, sleep), and clinical comorbidities (hypertension, diabetes. Additionally, multiple studies have demonstrated the high prevalence of weight gain in the United States population and detailed the signi cant medical consequences of obesity related diseases such as coronary artery disease and type II diabetes [11][12][13][14][15][16][17] . Despite the recognition of long-term weight gain as an important public health issue, there is a paucity of studies studying the long-term weight gain and building models for long-term projection.…”
Section: Introductionmentioning
confidence: 99%